2016
DOI: 10.1016/j.pedn.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder and the Child's Weight–Related Behaviors: A Parents' Perspective

Abstract: Implementation of healthy weight-related behaviors can be optimized when providers consider the child's challenging ASD behaviors, affirm the difficulties encountered by the family and provide guidance that builds on the individual child/family strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
(22 reference statements)
2
16
0
1
Order By: Relevance
“…Another potential factor is the child's preferences for certain tastes and preferences for processed foods or avoidance of foods such as vegetables. Changing or integrating new foods into the child's diet is often very difficult and may not be the foremost challenge that a parent wants to face or is able to do on a daily basis (Polfuss et al, 2016). As the child continues to eat certain foods, the habits can become engrained and create additional barriers to changing the child's diet in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another potential factor is the child's preferences for certain tastes and preferences for processed foods or avoidance of foods such as vegetables. Changing or integrating new foods into the child's diet is often very difficult and may not be the foremost challenge that a parent wants to face or is able to do on a daily basis (Polfuss et al, 2016). As the child continues to eat certain foods, the habits can become engrained and create additional barriers to changing the child's diet in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While there is not a recommendation that works for all children, parents of children diagnosed with autism spectrum disorder have identified strategies that have worked for their children when introducing new foods. Examples included diligent attempts at introducing new foods throughout their child's life but emphasized the need to start earlier and providing the same, albeit healthier options daily (Polfuss et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with ASD often have other co-morbid issues, such as seizures, chronic constipation, sleep disturbances that parents and providers may prioritize above weight management. Also, while some parents truly may not perceive their child’s weight as a concern, parents of children with ASD frequently have to “choose their battles” and make decisions led by the desire to prevent a negative behavioral response from their child (Polfuss et al, 2016). This may lead to parents accepting the potential consequences of not making changes in the child’s diet or physical activities in order to avoid behavioral problems or meltdowns and subsequently deprioritize weight management.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pan (2009) suggested that physical activity for children with ASD was affected more by social and environmental constraints rather than the impairment of ASD itself. On the contrary, Polfuss et al (2016) indicated that parents of children with ASD suggested certain characteristics of their children (i.e., lack of coordination and social abilities) affected their participation in structured sports. Additionally, Thompson et al (2010) found that parents played key roles in supporting their children's participation in physical activity indicating another potential influential factor in physical activity participation for children with ASD.…”
Section: Introductionmentioning
confidence: 99%